Fluoxetine removal by anodic oxidation using different anode materials and graphite cathode - Erkan, Hanife Sari; Kaska, Deniz; Kara, Narin; Engin, Guleda Onkal (TAYLOR & FRANCIS LTD, 2024)
Fluoxetine (FLX) is a selective serotonin reuptake inhibitor (SSRI) medication commonly used to treat mental health disorders, but it can be harmful to the environment if not properly disposed of due to incomplete metabolism. In this study, electrochemical anodic oxidation with mixed metal oxide anodes was studied as a method to remove FLX from water and wastewater. Iridium dioxide-coated titanium (Ti/IrO2) and ruthenium dioxide-coated Ti (Ti/RuO2) electrodes were found to be more effective than platinum-coated Ti (Ti/Pt) electrodes, with removal efficiencies of 91.5% and 93.9%, respectively. Optimal conditions for FLX removal were determined to be an applied current of 150 mA, initial pH of 5, and oxidation time of 120 min. The rate of FLX degradation (k(FLX)) for the Ti/Pt, Ti/IrO2, and Ti/RuO2 electrodes were determined to be 0.0081 min(-1) (R-2:0,8161), 0.0163 min(-1) (R-2:0,9823), and 0.0168 (R-2:0,9901) min(-1) for 25 mg/L initial FLX concentration, respectively. The k(FLX) values varied based on the initial FLX concentration and decreased as the initial FLX concentration increased. The specific energy consumption (SEC) after 120 min of operation was 51.0 kWh/m(3) for the Ti/Pt electrode, 39.6 kWh/m(3) for the Ti/IrO2 electrode, and 48.6 kWh/m(3) for the Ti/RuO2 electrode under optimised conditions. Overall, electrochemical anodic oxidation is an effective method for removing FLX from water and wastewater, with Ti/IrO2 and Ti/RuO2 electrodes providing superior performance compared to Ti/Pt electrodes.
Keywords: Electro-oxidation; anodic oxidation; fluoxetine (FLX); mixed metal oxide (MMO) anode; graphite cathode; BORON-DOPED DIAMOND; ELECTRO-FENTON DEGRADATION; WASTE-WATER; ELECTROCHEMICAL DEGRADATION; MASS-SPECTROMETRY; ACUTE TOXICITY; BY-PRODUCTS; PHARMACEUTICALS; MINERALIZATION; HYDROCHLORIDE; Environmental Sciences & Ecology